Parasitoses e desempenho animal: estudo meta-analítico em frangos de corte e suínos em crescimento - Silva, Marcos Kipper da (2011)
Two studies were carried out to evaluate, trough meta-analysis, the relationship between parasitosis and animal performance of broiler and growing pigs. Databases totaled 43,976 broilers (69 articles published between 1982 and 2010) and 1,279 growing pigs (18 articles published between 1971 and 2010). Meta-analyses followed three sequential analyses: graphic, correlation and variance-covariance. Pigs challenged by endoparasites presented reduction (P<0.001) of 5% on feed intake and 31% on weight gain. Broilers challenged by E. acervulina and E. tenella presented feed intake similar (P>0.05) to control group. However, the groups challenged by E. maxima and Pool presented increase on feed intake by 27% and 5% compared to control group. In relation to broilers weight gain, all challenged groups presented reduction (P<0.05) compared to control group. The average reduction was 10%, with the exception of the group challenged by E. maxima which showed a 23% reduction in daily weight gain compared to control group. The average age and average body weight of challenged animals, and the crude protein intake were the variables that most adjusted the determination coefficient in the equations for estimating the weight gain of parasitized pigs. Considering parasitized broilers, the reduction in feed intake was the variable that best explains the reduction in weight gain. Variance decomposition showed that parasitosis were responsible by a 6% reduction in weight gain for pigs and coccidiosis were associated by less than 1% for broilers. In addition, this analysis showed that most of the variation in weight gain was explained by the variation in feed intake (59% in pigs and 91% in broilers, on average). Parasitosis influences the performance of broilers and pigs. However, the magnitude of these effects varies with the parasite species, sex, age and line of the animal as well as nutritional factors.